DSF-family quorum sensing signal-mediated intraspecies, interspecies, and inter-kingdom communication - He, Ya-Wen (2022)
While most bacteria are unicellular microbes they communicate with each other and with their environments to adapt their behaviors. Quorum sensing (QS) is one of the best-studied cell-cell communication modes. QS signaling is not restricted to bacterial cell-to-cell communication - it also allows communication between bacteria and their eukaryotic hosts. The diffusible signal factor (DSF) family represents an intriguing type of QS signal with multiple roles found in diverse Gram-negative bacteria. Over the last decade, extensive progress has been made in understanding DSF-mediated communication among bacteria, fungi, insects, plants, and zebrafish. This review provides an update on these new developments with the aim of building a more comprehensive picture of DSF-mediated intraspecies, interspecies, and inter-kingdom communication.